2022
DOI: 10.1002/jbm4.10696
|View full text |Cite
|
Sign up to set email alerts
|

Greater pQCT Calf Muscle Density Is Associated with Lower Fracture Risk, Independent of FRAX, Falls and BMD: A Meta‐Analysis in the Osteoporotic Fractures in Men (MrOS) Study

Abstract: We investigated the predictive performance of peripheral quantitative computed tomography (pQCT) measures of both calf muscle density (an established surrogate for muscle adiposity, with higher values indicating lower muscle adiposity and higher muscle quality) and size (cross-sectional area [CSA]) for incident fracture. pQCT (Stratec XCT2000/3000) measurements at the tibia were undertaken in Osteoporotic Fractures in Men (MrOS) United States (US), Hong Kong (HK), and Swedish (SW) cohorts. Analyses were by coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Aside from the comprehensive inclusion of demographic, lifestyle, and clinical covariates, the main strength of our study is the use of accurate imaging techniques to quantify volumetric BMD and bone structure (HR‐pQCT), muscle mass (D 3 Cr), and muscle density (HR‐pQCT), all of which independently predict fractures. ( 1,2,17 ) This is in contrast to previous studies ( 10,11,14,29‐31 ) that used inferior imaging techniques such as DXA lean mass (a surrogate measure of muscle mass) that show inconsistent associations with fractures. ( 12,13 ) A recent study ( 7 ) also showed that older women with osteosarcopenia (defined as osteoporosis plus low grip strength and/or chair rise time by EWGSOP2) had significantly lower HR‐pQCT cortical bone parameters but similar DXA values when compared with osteoporosis alone.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Aside from the comprehensive inclusion of demographic, lifestyle, and clinical covariates, the main strength of our study is the use of accurate imaging techniques to quantify volumetric BMD and bone structure (HR‐pQCT), muscle mass (D 3 Cr), and muscle density (HR‐pQCT), all of which independently predict fractures. ( 1,2,17 ) This is in contrast to previous studies ( 10,11,14,29‐31 ) that used inferior imaging techniques such as DXA lean mass (a surrogate measure of muscle mass) that show inconsistent associations with fractures. ( 12,13 ) A recent study ( 7 ) also showed that older women with osteosarcopenia (defined as osteoporosis plus low grip strength and/or chair rise time by EWGSOP2) had significantly lower HR‐pQCT cortical bone parameters but similar DXA values when compared with osteoporosis alone.…”
Section: Discussionmentioning
confidence: 85%
“…Findings revealed no consistent interactions between these measures of musculoskeletal health in predicting these adverse outcomes. The basis of this analysis was that (i) both low BMD and low muscle mass or muscle density independently increase the risk of fractures in previous MrOs studies (1,2,17) and thus there may be an synergistic effect on fracture risk and (ii) both tissues can impact one another through biomechanical and biochemical mechanisms (6) and thus there may be an interactive effect on fracture risk (eg, in men with very low BMD the impact of muscle on the risk of fracture may be stronger than in those with higher BMD and vice versa). Indeed, evidence (largely from animal work) shows that bone and muscle are influenced by the same factors (such as physical activity, nutrition, and disease states) and affected by local cross-talk between bone, muscle, and fat cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations